EVALUASI PENILAIAN KAPASITAS SISA JEMBATAN LAWANG TADJI - N. Retno Setiati; Setyo Hardono (Jurnal Jalan-Jembatan, 2006)
Bridge is transportation infrastructure and connection of some areas, either in land, sea, river, or mountain have to fulfill planning criteria. Among bridge planning criteria a i.e. standard of strength, inertia, stability, security, and ride ability. Assessment of bridge residual value or capacities are very important in a scheme of repair and bridge rehabilitation, or whether a bridge is properly used or not. The girder of bridge in general one with slab of bridge. Therefore, the approach used to calculate capacities of cross section is T girder. Capacity of T girder is evaluated with ultimate strength concept. This theory has proven through experiment by many experts, and close to actual condition.